Global hepatitis B and D community advisory board: expectations, challenges, and lessons learned - Borondy-Jenkins, Fiona; Ansah, Bright; Chen, Jacki; Goldring, Amanda; Ibrahim, Yasmin; Issa, Shaibu; Lesidrenska, Silvana; Machado, Tanya; Moore, Holly; Njouom, Richard; Okinedo, Prince; Racho, Rhea; et al. (Frontiers in Public Health, 2024)
Introduction Community Advisory Boards (CABs) play an important role in developing and delivering patient-centered care. However, the impact of participation on CAB members has not been well studied, particularly on the global scale. In 2022, the Hepatitis B Foundation (HBF) convened the first global hepatitis B and hepatitis delta CAB with 23 members from 17 countries, representing six out of the seven World Health Organization (WHO) regions, and countries with the largest hepatitis B and hepatitis delta disease burden. Methods To reflect on the process of assembling an effective and motivated CAB and assess the impact on CAB participants, three virtual focus group sessions were held with 16 participants in July and August 2023. Sessions were recorded and transcribed. Questions focused on motivations for joining the CAB, membership experiences, and lessons learned. Grounded theory analysis was used to generate hypotheses about reasons for CAB members’ participation, as well as challenges and suggestions. Qualitative analysis using inductive reasoning identified key themes within responses. Transcripts were independently analyzed by a primary and secondary coder. Results Motivations for joining the CAB included participants’ desire to advocate for people living with hepatitis B and hepatitis delta, and other altruistic factors. Participants reflected that through CAB membership, they gained networking and advocacy opportunities and enhanced their hepatitis B- and hepatitis delta-related knowledge. Challenges participants experienced were related to time, physical limitations, and stigma. Finally, participants discussed their limited direct engagement with drug developers and proposed ways the CAB can increase interactions with stakeholders going forward. Discussion Based on participants’ assessments, establishing a global CAB for stigmatized infectious diseases is worth the effort. Regular internal review of community advisory boards’ structure and performance is critical to ensure the CAB is fulfilling its mission.